Synthesis and Characterization of Chitosan/PVA Composite Membranes with ZnO:Al for Adsorption-Photocatalysis of Methylene Blue Dye - Khabibi Khabibi; Trisna Bungah Alifa Rahman Singgong; Desita Putri Anggarini; Nor Basid Adiwibawa Prasetya; Retno Ariadi Lusiana (Jurnal Kimia Riset, 2026)
This study explored the synthesis of chitosan/PVA membranes modified with aluminium-doped ZnO (ZnO:Al) as the adsorption-photocatalysis of methylene blue (MB). The ZnO:Al nanocomposites were synthesized by the sol-gel method and then combined with chitosan to form membranes via the phase-inversion method. The nanocomposite was characterized using UV-Vis DRS, XRD, and FTIR. In contrast, the membrane was characterized by FTIR, SEM-EDX and tested for physical properties, including weight, thickness, swelling, water uptake, porosity, and hydrophilicity. The UV-Vis DRS results showed that the band gap of ZnO:Al was 2.93 eV, while the XRD results showed a shift in the diffraction peak at an angle of 2θ = 31.722°, 34.425°, and 36.233°, with a crystallite size of 14.8 nm. The FTIR spectrum of the membrane showed a shift in the band from 2876 cm⁻¹ to 2866 cm⁻¹ and the appearance of a peak at 463 cm⁻¹, indicating the presence of Zn–O groups. SEM analysis showed that the membrane surface was rougher than the membrane without filler, and EDX confirmed the presence of Zn, O, and Al. Adsorption-photocatalysis testing of the MB showed that the chitosan/PVA/ZnO:Al 1 membrane (composed of a gram ratio of chitosan/PVA/ZnO:Al of 1.5, 1.5, and 0.15 g, respectively) provided the highest degradation efficiency of 93.07%. These results indicate that the membrane has high potential for dye-based wastewater treatment applications.